2011
DOI: 10.1111/j.1468-005x.2011.00262.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the UK have a ‘comparative institutional advantage’ that is supportive of the IT services sector?

Abstract: This paper applies a 'sector-in-country' approach to examine the institutional conditions associated with the recent expansion of the information technology services sector in the UK. The findings reveal both synergies and tensions between the business and employment conditions of the sector and the wider institutional characteristics of the UK employment model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The changing nature of ICT work in the UK can clearly be seen in Table , demonstrating a gradual shift not only from more routinised to higher level work but also heralding a change in the nature of skills from technical knowledge to a combination of technical and soft/managerial skills. This shift has enabled UK firms to expand services rapidly but has also raised questions on the forms and combinations of skills required for entry (Donnelly et al ., ).…”
Section: Changing Nature Of Ict Work and Skillmentioning
confidence: 97%
See 1 more Smart Citation
“…The changing nature of ICT work in the UK can clearly be seen in Table , demonstrating a gradual shift not only from more routinised to higher level work but also heralding a change in the nature of skills from technical knowledge to a combination of technical and soft/managerial skills. This shift has enabled UK firms to expand services rapidly but has also raised questions on the forms and combinations of skills required for entry (Donnelly et al ., ).…”
Section: Changing Nature Of Ict Work and Skillmentioning
confidence: 97%
“…Education provision for ICT workers has expanded alongside demand for skills, although Marks and Huzzard (: 171) cite data from e‐skills, which notes ‘ a substantial fall in those with IT‐related degrees entering professional work from 47 per cent in 2000 to 28 per cent in 2004 ’, reflecting the need for a broader skills base to work in the sector (as opposed to a narrow focus on technical skills). Alongside this trend, there is evidence of a decline in applications to IT courses (Donnelly et al ., ). Adams and Demaiter () suggest that although credentialed knowledge and skills are established in the sector, technical skills can be acquired through routes other than IT‐related degrees reflecting a potential disconnect between the education provided by universities and industry requirements.…”
Section: Changing Nature Of Ict Work and Skillmentioning
confidence: 97%
“…So the relatively high graduate unemployment rates for computing (HESAb 2016) are something of a conundrum (Smith 2016). Efforts to explain the phenomenon include a recognition of the wide range of roles available to computing graduates, combined with the many and diverse skills expected by their employers (Fincher & Finlay 2016), as well as the off-shoring of technology industry jobs, especially in the UK context (Donnelly, Grimshaw, & Miozzo, 2011). Furthermore, it has been suggested that computing students may be more interested in gaining technical skills than acquiring diverse professional skills: for example, university staff in Fincher and Finlay's study (2016) observed that their students were instrumentally motivated by their love of computers and coding, rather than their career prospects.…”
Section: Work Experience Employability and Social Mobilitymentioning
confidence: 99%
“…Donnelly et al (2011) show that collective social actors in the UK largely failed in their attempt to professionalise the workforce in the IT services sector through joint investment in training, due to weak coordination among the actors and marginal support from firms. In contrast, Kuruvilla and Ranganathan (2010) found that in the Indian business process outsourcing industry, high turnover rates among an increasingly mobile, middle-class workforce led companies to experiment with new HRM strategies aimed at improving recruitment, retention and training.…”
Section: Challenges Of Hrm Coordinationmentioning
confidence: 99%
“…Yu and Levy (2010) found that radiology professionals working in the Indian offshore sector experienced a deskilling of their work, with negative effects on worker motivation. Another recent UK study found that increased internationalisation of the value chain for IT services contributed to a falling domestic demand for technical IT skills, with negative effects on career development and professionalisation in the sector (Donnelly et al 2011).…”
Section: Challenges Of Hrm Coordinationmentioning
confidence: 99%